Negative self-evaluation and the genesis of internal threat: beyond a continuum of suicidal thought and behaviour. Issue 15 (3rd December 2018) - Butter, Sarah; Shevlin, Mark; Murphy, Jamie
Abstract: Background: Death by suicide is often preceded by attempted suicide, suicidal ideation and non-suicidal self-injury. These extreme thoughts and behaviours have been considered in terms of a continuum of suicidality. Little known research, however, has considered a suicide continuum that extends beyond these extreme thoughts and behaviours and incorporates a much wider array of phenomena that may vary in severity and may constitute a broader negative self-evaluation (NSE) continuum. Method: Harvesting key indicators of NSE from a British epidemiological survey ( N = 8580), the current study used exploratory factor analysis, confirmatory factor analysis and factor mixture modelling to (i) identify the dimensional structure of NSE in the general population and (ii) profile the distribution of the resultant NSE dimensions. Multinomial logistic regression was then used to differentiate between classes using an array of risk variables, psychopathology outcome variables and a suicide attempt indicator. Results: A 4-factor model that reflected graded levels of NSE was identified; (F1) Low self-worth & subordination (F2) depression, (F3) suicidal thoughts, (F4) self-harm (SH). Seven classes suggested a clear pattern of NSE severity. Classes characterised by higher levels across the dimensions exhibited greater risk and poorer outcomes. The greatest risk for suicide attempt was associated with a class characterised by engagement in SH behaviour. Conclusions: Low self-worth, subordination and depression, while representative of distinct groups in the population are also highly prevalent in those who entertain suicidal thoughts and engage in SH behaviour. The findings promote further investigation into the genesis and evolution of suicidality and internal threat.